Association of Epicardial Fat Volume with Coronary Artery Ectasia and Coronary Artery Disease. (July 2023) - Subhan, Shoaib; Sami, Abdul; Akhtar, Waheed; Jan, Muneeb Ullah; Ullah, Asif; Malik, Jahanzeb
Epicardial fat may play an important role in the pathogenesis of coronary artery disease (CAD). We investigated the relationship between coronary artery ectasia (CAE) and epicardial fat volume (EFV). This retrospective study included 506 patients with CAE (group 1), 500 with CAD (group 2), and 500 patients with normal coronaries as controls (group 3). The pericardium was traced manually from the edge of the pulmonary trunk to the last measured by computed tomography slice containing images of the heart to obtain a region of interest. EFV was significantly higher in patients with CAD than in those with CAE (87.94 ± 22.18 vs 61.33 ± 12.75 mL; P < .001). Patients with normal coronaries had EFV of 56.62 ± 9.82 mL. Multivariate logistic regression analysis showed that male gender [Odds ratio (OR) (95% confidence interval (CI)): 1.220 (1.015–1.682), P = .042], diabetes [OR (95% CI): 1.036 (1.008–1.057); P = .002], and smoking [OR (95% CI): 3.043 (1.022–9.462); P = .005] were significantly associated with CAE. The receiver operating characteristic (ROC) curve showed that EFV had strongest diagnostic value for detecting CAD rather than CAE [AUC .502 P = .074 (95% CI: .311–.784)]. This study demonstrated that EFV is an independent predictor for CAE and CAD. However, sensitivity and specificity for detecting CAE is low when compared with CAD.